Avaliação in vitro de superfícies de titânio irradiadas com laser de Er,Cr:YSGG - Coletti, Felipe Leite; Theodoro, Letícia Helena; Marcantonio, Adriana Rosemary Chierici [UNESP]; Marcantonio Júnior, Elcio [UNESP]; Garcia, Valdir Gouveia [UNESP] (My University, 2011)
Introduction: As a new alternative in the complementary treatment lasers teem different systems were employed in the decontamination of dental surfaces implants however, some systems have caused significant changes in its surface. Purpose: Analyze by Scanning Electron Microscopy (SEM) the effects of laser irradiation of Er,Cr: YSGG on different surfaces of titanium. Material and method: Study of 20 titanium discs, and 10 Machined Surface (MS) and 10 surfaces treated with acid (AC). The 10 discs with the same treatment were divided into two groups with five units each, the irradiation was performed in powers of 1 W and 2 W. Result: Showed that the irradiation with 1 W of power resulted in no significant morphological changes in the MS-irradiated compared to non-irradiated surfaces. In MS surfaces, minor changes were observed in the increase of 1000× when compared to non-irradiated surface. With 2 W of power, there were no significant morphological changes in the MS, compared to non-irradiated areas. In AC some changes were observed in the increase of X 1000, showing areas of wear suggestive of treatment and some areas with melting point. Conclusion: Considering the results and the parameters used in this study it was concluded that the Er, Cr: YSGG irradiation can be used for the machined surfaces of implants, but in acid-treated surfaces irradiation parameters should be more controlled.

Introdução: Como uma nova alternativa no tratamento complementar, diferentes sistemas lasers têm sido empregados na descontaminação de superfícies de implantes dentários; entretanto, alguns sistemas promoveram alterações significantes nessas superfícies. Objetivo: O propósito deste estudo foi analisar, por meio de microscopia eletrônica de varredura (MEV), os efeitos da irradiação de diferentes superfícies de titânio com o laser de Er,Cr:YSGG (Erbium, Chromium, Yttrium, Scandium, Gallium, Garnet). Material e método: Foram utilizados 20 discos de titânio, sendo dez de Superfície Usinada (SU) e dez de Superfície tratada com Ataque Ácido (SAC). Os dez discos com mesmo tratamento foram divididos em dois grupos, que receberam irradiação nas potências de 1 W (5 unidades) e 2 W (5 unidades). As superfícies foram analisadas por meio de MEV. Resultado: Com 2 W de potência, não foram observadas alterações morfológicas significantes nas SU, quando comparadas às superfícies não irradiadas. Nas SAC, algumas alterações foram observadas no aumento de 1000×, apresentando áreas sugestivas de desgaste do tratamento além de algumas áreas com aspecto de derretimento. Conclusão: Diante dos resultados e com os parâmetros utilizados no presente estudo, conclui-se que o laser de Er,Cr:YSGG pode ser utilizado para irradiações de superfícies usinadas de implantes; porém, em superfícies tratadas com ácido, os parâmetros de irradiação devem ser mais controlados.
In vitro evaluation of titanium surfaces treated with Er,Cr:YSGG laser
Keywords: Lasers; Dental implants; Scanning electron microscopy; Lasers; Implantes dentários; Microscopia eletrônica de varredura